2022
DOI: 10.1007/s00027-022-00899-8
|View full text |Cite
|
Sign up to set email alerts
|

Redox conditions and a moderate anthropogenic impairment of groundwater quality reflected on the microbial functional traits in a volcanic aquifer

Abstract: Groundwater is an important freshwater resource and hosts specialized microbial assemblages providing fundamental ecosystem services. The current knowledge on the role of aquatic microorganisms in subsurface ecosystems is still limited. This work aimed to explore the links between groundwater hydrogeochemical properties and microbial community traits in a volcanic unconfined aquifer, moderately impacted by anthropic activities. The main physical and chemical parameters of groundwater samples were analyzed, alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Our analyses indicated that the sulfate-depleted GWB had the highest proportions of microbes metabolizing polymers, which are more complex and resistant to degradation than simple carbohydrates or carboxylic acids (Oest et al, 2018;Melita et al, 2019). Additionally, we observed variations in the proportions of microbes utilizing different substrates from year to year, likely influenced by surface-produced organic matter types (Saccò et al, 2019;Melita et al, 2023). Our finding suggests that the sulfate-depleted GWB may lack the necessary energy resources to sustain a resident crustacean assemblage.…”
Section: Discussionmentioning
confidence: 62%
“…Our analyses indicated that the sulfate-depleted GWB had the highest proportions of microbes metabolizing polymers, which are more complex and resistant to degradation than simple carbohydrates or carboxylic acids (Oest et al, 2018;Melita et al, 2019). Additionally, we observed variations in the proportions of microbes utilizing different substrates from year to year, likely influenced by surface-produced organic matter types (Saccò et al, 2019;Melita et al, 2023). Our finding suggests that the sulfate-depleted GWB may lack the necessary energy resources to sustain a resident crustacean assemblage.…”
Section: Discussionmentioning
confidence: 62%